The Effect of Multipass Strategy in Teaching Reading on Students’ Reading Comprehension - Putri Nabila Aisyah; Burhanuddin Yasin; Ika Apriani Fata (Universitas Syiah Kuala, 2021)
This research aims to look at the effect of the Multipass strategy in teaching reading on students’ reading comprehension (A Library Research). The Multipass strategy and reading comprehension function as the independent variable and dependent variable consecutively. The Multipass strategy is a teaching strategy that aims to increase students' reading ability by using three main procedures; survey-pass, size-up pass, and sort-out pass. The researcher focuses on the lack of students' reading comprehension and aims to find out the effectiveness of the Multipass strategy to improve students' reading comprehension skills. The method of this study is library research and the data attached in this research are obtained from the previous works of the other researchers and some literature sources include journals, books, articles, and internet websites. The data analysis technique includes the process of data identification from relevant literature sources, determining where the data are located, obtaining the data, evaluating the data, and incorporating data into the research presentation. The results of this study show that the students reading comprehension skills were improved after they were given the treatment of the Multipass strategy using ten teaching instructions and the three Multipass main procedures (survey-pass, size-up pass, and sort-out pass). The results were proven by the students' test scores and validity tests. To sum up, the Multipass strategy is considered as the teaching strategy to improve students' reading comprehension skills.